Conflict, Negotiation, and Organizational Change: Building an Adaptive Organization in the Face of Strategic Environmental Dynamics - Rahmad Asril Pohan; Anang Anas Azhar (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Organization contemporary face problematic fundamental in the form of difficulty manage interaction between conflict, negotiation, and change in a way integrated in build capacity adaptive face dynamics environment increasingly strategic volatile. Many organizations trapped in paradox where conflict arises from initiative change precisely nature destructive, while negotiations carried out tend compromising and not transformative. Research This aim For analyze and synthesize relatedness between conflict, negotiation, and change organization in framework build organization adaptive. Method research used is studies library with data sources in the form of book international and national as well as article journal reputable. Data analysis techniques using analysis content qualitative combined with approach analysis thematic and synthesis narrative. Research results disclose four findings main. First, conflict organizational in context environment strategic contemporary is catalyst that when managed in a way constructive can stimulate innovation and strengthening resilience organization. Second, negotiation strategic has evolve from mechanism distributive become instrument transformative through approach integrative and deliberative dialogue. Third, design architecture effective change requires shift from approach episodic going to change integrated sustainability with context strategic. Fourth, synthesis the three domains produce organizational models adaptive characterized by double - loop learning, structure organization fluid, and leadership distributed. Implementation directed at institutionalizing a debate forum strategic, integration training negotiation transformational in curriculum leadership, recalibration system management performance, as well as transformation structural going to design supported modular organization digital infrastructure.